Sexually transmitted infections in pregnancy: prevalence, impact on pregnancy outcomes, and approach to treatment in developing countries. Issue 4 (1st August 2005) - Mullick, S; Watson-Jones, D; Beksinska, M; Mabey, D
Abstract : Sexually transmitted infections (STIs) are common in the developing world. Management of STIs in pregnancy in many developing countries has, however, been complicated by the lack of simple and affordable diagnostic tests. This review examines the prevalence and impact on pregnancy outcome of STIs in developing countries and recommends approaches to management of STIs in pregnancy for resource poor settings.